COMMUNITY SECURITY IN TEMUR'S LAWS COLLECTION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article tells about the work done by Amir Temur to ensure public safety in the country, that is to say the role of the administrative (cabinet, ministries, governors, etc.) and financial system in ensuring public safety, socio-political and economic stability, the rule of law, and social justice were also highlighted.